PEMBENTUKAN PORTOFOLIO OPTIMAL PADA PERUSAHAAN KEUANGAN DI BEI - Prayogo, Ardyan; Ariyani, Vivi (JRMA | Jurnal Riset Manajemen dan Akuntansi, 2013)
Investors need the investment risk minimizing. Investment diversification can be realized by combining a variety of securities in the investment, in other words, investors form portfolios.This study aims to examine the optimal portfolio combinations formed from some financial company shares with the observation period January 2008 - June 2011. This study used a single index model method. Purposive sampling technique is applied to choose sample. This study used secondary data derived from the financial statements provided in the Indonesia Stock Exchange, the market index (JCI) obtained from yahoofinance, and data rate FASBI obtained from Bank Indonesia.